Red Schools, Blue Schools? Republican and Democratic Student Groups at U.S. Colleges and Universities. Issue 1 (7th December 2022) - Coley, Jonathan S.; McElroy, Jericho R.; Schachle, Jessica L.
Abstract : How prevalent are Republican and Democratic student groups, and why are some schools home to Republican and Democratic student groups while other schools are not? Some commentators and scholars suggest that Republican student groups may be less prevalent than Democratic student groups and, when present, will likely be found at "red schools" (rather than "blue schools") in Republican‐leaning areas of the country. However, other scholars argue that both Republican and Democratic student groups should be similar in their overall prevalence and located at a similar set of "engaged schools" (as opposed to "unengaged schools"). Analyzing our original database of Republican and Democratic student organizations across 1, 953 four‐year, not‐for‐profit U.S. colleges and universities, we first show that Republican student groups are nearly as common as Democratic student groups: Republican student groups can be found at 39% of campuses, while Democratic student groups are present on 40% of campuses. Employing binary and multinomial logistic regression analyses, we then show that Republican and Democratic student groups tend to be located at the same types of schools, that is, larger, wealthier, public schools that offer political science majors. Our article holds significant implications for theorizing on student organization presence more generally.